(untitled) (Research, Society and Development, 2021)
This work presents a review of the book: "Vygotsky, Leontiev and Galperin: formation of didactic concepts and principles". The book was written by Isauro Beltrán Núñez and covers the formation of concepts in the theoretical perspective of Vygotsky, Leontiev and Galperin, presenting a description of the didactic principles assumed from the analysis of Historical-Cultural Theory, Activity Theory and Theory of Assimilation. For this, the formative itinerary of the theories proposed by Vygotsky, Leontiev and Galperin was presented, highlighting the aspects in which they complement and diverge. Therefore, the author highlighted the relevance of didactic planning with a focus on Assimilation Theory in conjunction with the stages of Historical-Cultural Activity for teaching and learning practice. Finally, we sought to encourage the reader to reflect on the possibility of articulating Galperin’s conceptions with other sociocultural theories, such as, for example, the Theory of Objectification by Luis Radford, which has many implications for the teaching of Science and Mathematics, with a view way, its extension to other areas of knowledge.